The Role of Artificial Intelligence in Website Encryption - Fahad Al-Zahrani,; Nabil Al-Shahrani,; Faisal AL-GHAMDI, (International Journal of Computers and Informatics, 2025)
The rapid advancement of digital services and the increasing reliance on internet-based transactions have highlighted the crucial need for robust cybersecurity measures. Encryption is a fundamental technique used to secure sensitive data, preventing unauthorized access and data manipulation. However, traditional encryption methods face limitations in adapting to evolving cyber threats. Artificial Intelligence (AI) has emerged as a transformative force in enhancing encryption techniques, leveraging deep learning, neural networks, and predictive analytics to provide dynamic and adaptive encryption solutions. This paper explores the role of AI in website encryption, focusing on its contributions to smart encryption, real-time threat detection, and the enhancement of encryption protocols such as TLS and SSL. Additionally, the study examines the challenges associated with AI-driven encryption, including high computational resource requirements, the risks of AI-powered attacks, and implementation complexities. As AI continues to evolve, its integration into encryption methodologies is expected to play a pivotal role in strengthening cybersecurity frameworks and mitigating emerging cyber threats.
Keywords: Artificial Intelligence; Encryption; Cybersecurity; Machine Learning; Smart Encryption; Threat Detection; Security Protocols